User’s Manual: How to Demonstrate Liberal Humanism without Falling into a Trap of Genealogy - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2006)
Review: Bielskis, Andrius. 2005. Towards a Post-Modern Understanding of the Political: From Genealogy to Hermeneutics. Palgrave Macmillan.